Civil Law and Environmental Protection: Expanding Liability for Sustainable Justice - Haq, Miftahul (RIGGS: Journal of Artificial Intelligence and Digital Business, 2025)
Environmental degradation has emerged as one of the most pressing global challenges, demanding stronger legal frameworks to ensure accountability and sustainability. Within civil law systems, the expansion of liability principles plays a crucial role in addressing environmental harm by holding individuals, corporations, and even state actors responsible for ecological damages. This study examines the intersection between civil law and environmental protection, with a focus on how liability doctrines—such as strict liability, fault-based liability, and collective responsibility—are evolving to support sustainable justice. By employing a normative legal research method combined with comparative analysis, this research highlights the adaptation of civil liability in various jurisdictions to respond to environmental risks, including pollution, deforestation, and climate change. The findings suggest that while traditional civil law mechanisms provide a foundation for redress, innovative approaches such as environmental compensation funds, extended corporate liability, and integration of precautionary principles are necessary to strengthen legal remedies. Ultimately, this study argues that expanding civil liability not only enhances deterrence and accountability but also promotes equitable and sustainable solutions for environmental governance in the 21st century.